The correlation between urinary 5-hydroxyindoleacetic acid and sperm quality in infertile men and rotating shift workers - Pariente José A; García Juan F; Lozano Graciela M; Monllor Fabián; Bejarano Ignacio; Espino Javier; Ortiz Águeda; Rodríguez Ana B (BMC, 2010)
Abstract Background Serotonin is a neurotransmitter that modulates a wide range of neuroendocrine functions. However, excessive circulating serotonin levels may induce harmful effects in the male reproductive system. The objective of this study was to evaluate whether the levels of urinary 5-hydroxyindoleacetic acid (5-HIIA), a major serotonin metabolite, correlate with different classical seminal parameters. Methods Human ejaculates were obtained from 40 men attending infertility counselling and rotating shift workers by masturbation after 4-5 days of abstinence. Urinary 5- HIIA concentration was quantified by using a commercial ELISA kit. Forward motility was assessed by a computer-aided semen analysis (CASA) system. Sperm concentration was determined using the haemocytometer method. Sperm morphology was evaluated after Diff-Quik staining, while sperm vitality was estimated after Eosin-Nigrosin vital staining. Results Our results show that urinary 5-HIIA levels obtained from a set of 20 volunteers negatively correlated with sperm concentration, forward motility, morphology normal range and sperm vitality. On the other hand, we checked the relationship between male infertility and urinary 5-HIIA levels in 20 night shift workers. Thus, urinary 5-HIIA levels obtained from 10 recently-proven fathers were significantly lower than those found in 10 infertile males. Additionally, samples from recent fathers exhibited higher sperm concentration, as well as better forward motility and normal morphology rate. Conclusions In the light of our findings, we concluded that high serotonin levels, indirectly measured as urinary 5-HIIA levels, appear to play a role as an infertility determinant in male subjects.